Intervensi Non Farmakologi untuk Menurunkan Kecemasan dan Ketakutan Persalinan pada Trimester III Kehamilan - Lantu, Nurlela; Rachmawati, Imami Nur; Kurniawati, Wiwit (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to identify non-pharmacological interventions that can reduce anxiety and fear during childbirth in the third trimester of pregnancy. Using the PRISMA method, the research method used is a systematic review through searching 6 (six) databases, namely ProQuest, Scopus, Pubmed, Science Direct, and Taylor & Francis. The results of research from 11 articles included in the analysis show that non-pharmacological interventions that can reduce pregnant women's anxiety levels regarding pregnancy and childbirth are providing education and training in preparation for childbirth carried out face to face (P < 0.001), Iyengar yoga (P < 0 .05), and the application of lavender oil as aromatherapy (P<0.001) as well as mindfulness-based antenatal education (P<0.001). Meanwhile, non-pharmacological interventions that can reduce the level of fear during childbirth are simulation-based childbirth preparation education combined with mindfulness (P<0.01), online-based antenatal education about childbirth preparation (P<0.05), Mindfulness-Based Childbirth and Parenting (MBCP) with a partner (P< 0.05), simulation-based childbirth education (P< 0.05), psychodrama (P< 0.001) and psychotherapy (P< 0.001). In conclusion, non-pharmacological interventions given to pregnant women in the third trimester of pregnancy can reduce the level of anxiety and fear of childbirth. Keywords: Non-Pharmacological Intervention, Anxiety, Pregnancy, Fear of Childbirth